Strategic Entrepreneurship Risk-taking on Technological Opportunism to Enhance Revenues and Manage Bank Viability in Competitiveness - Mabiza, Junior; Edoun, E.I.; Bakam, F.G.; Maphumulo, Mandlenkosi W. (Technium Social Sciences Journal, 2021)
The risk of relying on technology within organizations is whether it generates success and profits related to the objectives of the overall plan or no success and loss of objectives and finances in opposite. As a result, strategic entrepreneurship can be used to develop methods of asserting whether the introduction of new models or tools can lead to intended outcomes. Entrepreneurial strategy underpins several concepts that support the development of an outcome to expect from both entrepreneurial orientations and planning flexibility; in particular, risk-taking, responsiveness and innovation, which can be measured in the course of operations, in order to determine, if they exist, moderating and mediating factors between technological opportunism and performance of organisations achieving a high rate of success through a new product, revenue growth, ROI ( return on investment), substantial share of the market, or outstanding lucrativeness.This article investigated the technological opportunism effects on the performance of firm and the effects of mediating and moderating of risk taking in strategic entrepreneurship. The banking sector is the domain in which the influence of risk-taking was assessed using hypotheses.